2019
DOI: 10.1021/acs.jpclett.9b01499
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic DFT-1/2 Calculations Combined with a Statistical Approach for Electronic and Optical Properties of Mixed Metal Hybrid Perovskites

Abstract: We overcome the great theoretical computational challenge of mixed perovskites, providing a rigorous and efficient model by including quasiparticle, spin−orbit coupling, and disorder effects. As a benchmark, we consider the mixed MAPb 1−x Sn x I 3 perovskites. The calculations are based on the generalized quasichemical approach and the DFT-1/2 approximated quasiparticle correction. Both cubic and tetragonal structures are investigated. By mapping the entire range of compositions, we correctly describe the bowi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 50 publications
(83 reference statements)
1
33
0
Order By: Relevance
“…The calculations consider both the standard DFT approach and the DFT-1/2 quasiparticle correction to the PBE functional. DFT-1/2 is a correction approach , to the well-known underestimation in band gap of DFT that has shown to be successful in numerous perovskite systems. It consists of adapting the Kohn–Sham potential by removing the self-energy potential associated with the half-electron from the valence band maximum V S,VBM and then adding the same term for the half-electron in the conduction band minimum V S,CBM Equation is approximated by neglecting the CBM term. To prevent the potential from diverging due to the periodic charge disbalance, the correction term is multiplied by a trimming function of the form where CUT is a system-dependent length parameter obtained variationally, as described elsewhere. , For the unit cell calculations, we obtain values of 3.20 and 3.05 au for the corrections of the I p orbital in CsPbI 3 and CsSnI 3 , respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The calculations consider both the standard DFT approach and the DFT-1/2 quasiparticle correction to the PBE functional. DFT-1/2 is a correction approach , to the well-known underestimation in band gap of DFT that has shown to be successful in numerous perovskite systems. It consists of adapting the Kohn–Sham potential by removing the self-energy potential associated with the half-electron from the valence band maximum V S,VBM and then adding the same term for the half-electron in the conduction band minimum V S,CBM Equation is approximated by neglecting the CBM term. To prevent the potential from diverging due to the periodic charge disbalance, the correction term is multiplied by a trimming function of the form where CUT is a system-dependent length parameter obtained variationally, as described elsewhere. , For the unit cell calculations, we obtain values of 3.20 and 3.05 au for the corrections of the I p orbital in CsPbI 3 and CsSnI 3 , respectively.…”
Section: Methodsmentioning
confidence: 99%
“…20 Additionally, given the importance of the relativistic aspects of Pb in typical OIHP polymorphs, searching for substituents for the heavy and toxic lead using cleaner metals, such as Sn and Ge, sets an additional debate about the relationship between bulk Rashba and SOC effects. 21,22 This Letter shows how polymorphism affects the bulk Rashba splitting for MAPbI 3 , MASnI 3 , MAGeI 3 , and MASiI 3 in all 3D perovskite structures, i.e., cubic, tetragonal, and orthorhombic. Standard density functional theory (DFT) leads to a good bandgap description for OIHP; however, this is just an artificial effect.…”
mentioning
confidence: 90%
“…From that, and by using effective models, Zheng et al found that the long recombination time of the charge carriers is due to the slower transition rate thanks to the mismatch of spin and momentum due to the Rashba effect . Additionally, given the importance of the relativistic aspects of Pb in typical OIHP polymorphs, searching for substituents for the heavy and toxic lead using cleaner metals, such as Sn and Ge, sets an additional debate about the relationship between bulk Rashba and SOC effects. , …”
mentioning
confidence: 99%
“…The VPSIC approach used in this work was shown to be of accuracy similar to the very popular hybrid HSE hybrid functional, 67,68 albeit substantially less computationally demanding. An interesting alternative is represented by the DFT-1/2 method, 69 which was recently used for stannates, [70][71][72] and can be considered a simplied version of the VPSIC (a comparison of these two approaches can be found in ref. 73).…”
Section: Methodsmentioning
confidence: 99%